Impact of diet on irinotecan toxicity in mice. (1st August 2018) - Mallick, Pankajini; Shah, Pranav; Ittmann, Michael M.; Trivedi, Meghna; Hu, Ming; Gao, Song; Ghose, Romi
Abstract: Irinotecan is highly effective in the treatment of metastatic colorectal cancer as well as many other cancers. However, irinotecan is known to cause severe diarrhea, which pose significant problems in patients undergoing irinotecan based chemotherapy. Dietary and herbal components have shown promise in improving gastrointestinal health. Therefore, we compared the effect of grain-based chow diet containing phytoestrogens and corn/alfalfa as fat source to purified diets containing either animal-derived fat source (lard) or plant-derived fat source (soybean oil) on irinotecan-induced toxicities in mice. The concentration of the toxic metabolite, SN-38, was measured in the serum, and the activity of main enzyme, carboxylesterase (CEs) involved in biotransformation of irinotecan to SN-38 formation was measured in the liver. We found that the grain-based diet was protective against irinotecan-induced diarrhea. Interestingly, purified diet containing lard caused fatty liver in mice, while grain-based chow diet containing corn/alfa-alfa or purified diet with soybean oil did not cause fat deposition in the liver. Serum SN-38 concentration was significantly higher in the mice fed with purified diets compared to the chow-fed mice. Hepatic CEs activity was induced in the presence of irinotecan in mice on purified diets, but not chow diet. These results indicate that components of grain-based natural diet (presumably phytoestrogens and/or the macronutrients balance) compared to purified diets may have a beneficial effect by controlling the adverse effects of irinotecan in cancer patients. Highlights: Chow diet has protective effect against irinotecan-induced diarrhea and steatosis. Diarrhea and steatosis was associated with increased SN-38 serum levels. Carboxylesterase and β-glucuronidase enzyme activity was affected by diets. Protective effects of chow diet likely due to phytoestrogens, fibers, etc.